Factors predicting satisfaction in outpatient substance abuse treatment: a prospective follow-up study - Katja Kuusisto; Tomi Lintonen (BMC, 2020)
Abstract Background While treatment satisfaction has been associated with better outcomes in substance abuse treatment, there is an obvious need for a more profound understanding of what predicts client's satisfaction with treatment. This study elucidates factors relevant to treatment outcome measured at follow-up in terms of satisfaction with the treatment received. Methods The research was implemented as a multisite study in outpatient clinics (N = 7) in southern and western Finland. Data consists of therapists (N = 33) and their clients (N = 327). Each consenting client beginning a treatment period was accepted as a research subject and all therapists at the clinics in question participated. The study was conducted as part of the clinic's normal activity. Clients were allocated to therapists according to a randomization list drawn up in advance. Apart from the randomisation and the completion of questionnaires, it did not interfere with the progress of treatment. Follow-up lasted 6 months. Multiple Classification Analysis (MCA) was used through combinations of variables organized by content, e.g. client demographics, previous substance use, therapist's characteristics and client's expectations. The analyses were based in part on conventional statistical testing (t -test, χ 2-test, ANOVA). Results Among 37 independent variables few were statistically significant in the final model. The results suggest that high treatment expectations at baseline are a strong predictor of satisfaction at follow-up. Also, previous substance use predicted treatment satisfaction; people using multiple substances were less satisfied than those taking only one substance. Stronger predictors reduced the statistical significance of those independent variables that were statistically significant in the first analyses. Therefore, therapist's role in recovery and readiness to change should be also seen as antecedents to treatment satisfaction. Conclusions It seems that treatment expectations are fulfilled among those participating in follow-up. Yet many are lost during treatment and by follow-up. Service users have experiential knowledge that differs from professionals' and policymakers' knowledge. It is clinically relevant to understand what factors affect client's satisfaction. Hence, it is possible to identify the population whose treatment should receive the most attention, how the client's experience, their commitment to treatment, and treatment effectiveness could be improved.